Intelligence, Ignorance, and Diplomacy in the Cold War: The UK Reaction to the Sverdlovsk Anthrax Outbreak. Issue 1 (29th November 2021) - Balmer, Brian
Drawing on perspectives from "ignorance studies, " this article examines a case of multiple types of expertise and ignorance within the geo-political context of the Cold War. It revisits a suspected breach of the 1972 Biological Weapons Convention (BWC). In 1979, an outbreak of anthrax occurred in the Russian city of Sverdlovsk, killing numerous people; Sverdlovsk was also the site of a military facility suspected by the West of undertaking biological weapons research. As news of the outbreak reached the West, first the USA, then the UK approached the USSR seeking clarification. The diplomatic path followed by the two nations involved a tricky balancing act, requiring attention to the souring of East-West relations following the Soviet invasion of Afghanistan, the integrity of the BWC, and the remote possibility of ratifying the SALT II nuclear negotiations. Diplomatic tactics depended on epistemic issues: How to tell whether the disease outbreak was natural or a military accident, how to decide what evidence was needed? I argue that although officials and scientists did not welcome ignorance and uncertainty, they recognized it as an inevitable and highly problematic epistemological issue (can we know what happened?) and tempered it into a less problematic, or at least more manageable, pragmatic issue (is there sufficient evidence to follow a particular course of action?). This article is part of a special issue entitled "Histories of Ignorance, " edited by Lukas M. Verburgt and Peter Burke.